The Influence of Practicum Video with Electronic Module Toward Process Skills for Stoichiometry Materials of the Grade X of SMAN 2 Tidore Islands - Nur A Limatahu; Nurul Aulia Rahman; St Hayatun Nur Abu; Indra Cipta (Jurnal Pendidikan Kimia (JPKim), 2017)
Abstract: This study aimed to determine the effect of practicum video with electronics module toward process skills and how far the influence of stoichiometry materials of the grade X of SMA Negeri 2 Tidore Islands. This study used experiment research. The study design was experiment with One Group Pretest-Postest Design. The population was the grade X students of SMAN 2 Tidore Islands. The sample was class X1chosen randomly. Data analysis technique was through statistical descriptive analysis and inferential statistical analysis which used SPSS 16. The results of hypothesis testing showed that sig <0,05 and t count > t table then the use of practicum video and electronic modules influence the process skills of students. Gain value is 85% indicating a high interpretations to the improvement process skills of students. Keywords: process skills, electronics modul,  practicum video